2015
DOI: 10.1136/bjophthalmol-2014-306319
|View full text |Cite
|
Sign up to set email alerts
|

Ziv-aflibercept in macular disease

Abstract: Background/aimsAflibercept is an approved therapy for neovascular age-related macular degeneration (AMD) and diabetic macular oedema (DME). In vitro and in vivo studies did not detect toxicity to the retinal pigment epithelium cells using the approved cancer protein, ziv-aflibercept. Our purpose is to determine if ziv-aflibercept can be used in AMD and DME without ocular toxicity, to test the stability of ziv-aflibercept, and to do a cost analysis.MethodsProspectively, consecutive patients with AMD or DME and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
102
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(107 citation statements)
references
References 24 publications
2
102
0
3
Order By: Relevance
“…In a prospective noncomparative case series of 6 patients (4 with AMD and 2 with refractory diabetic macular edema), intravitreal ziv-aflibercept improved the visual acuity and decreased the central macular thickness. However, the follow-up was only 4 weeks [9] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a prospective noncomparative case series of 6 patients (4 with AMD and 2 with refractory diabetic macular edema), intravitreal ziv-aflibercept improved the visual acuity and decreased the central macular thickness. However, the follow-up was only 4 weeks [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Ziv-aflibercept is a similar fusion protein and has shown promising results in the short term [8,9,11] . In our previous study of intravitreal ziv-aflibercept for diabetic macular edema, all patients experienced improvement in BCVA and decrease in CRT from baseline till 24 weeks of follow-up [11] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some investigators contend that intravitreal injections of ziv-aflibercept solution may be toxic to the retina or uveal tract, but others believe that it might be safe and, therefore, useful against chorioretinal vascular conditions. 15 We believe that intravitreal ziv-aflibercept may be safe and effective when used in human eyes with neovascular AMD, and herein, we present a detailed safety evaluation using sequential clinical evaluations and electroretinographic (ERG) testing after single intravitreal injections.…”
mentioning
confidence: 99%
“…Clinical trial conducted by Malik et al [3] to address the safety issue of ziv-aflibercept in vivo and in vitro and concluded that there is non-significant RPE toxicity where, Mansour et al [4] has studied the safety of intravitreal Ziv-aflibercept in six patients and all patients, and the results didn't show any signs of retinal, ocular toxicity or inflammation and suggested that the 0.05 ml Ziv-aflibercept is diluted in 4 ml of vitreous when intravitreally injected, thus it is 80 times diluted which means the final osmolarity of 312 mOsm/kg after intravitreal injection of 0.05 ml Ziv-aflibercept, Masnour et al [5] also studied the safety and efficacy of intravitreal ziv-aflibercept in wet age related macular degeneration and concluded that intravitreal ziv-aflibercept can be safe and effective without causing any ocular toxicity. …”
Section: Discussionmentioning
confidence: 99%